2009
DOI: 10.1681/asn.2008050507
|View full text |Cite
|
Sign up to set email alerts
|

Unified Criteria for Ultrasonographic Diagnosis of ADPKD

Abstract: Individuals who are at risk for autosomal dominant polycystic kidney disease are often screened by ultrasound using diagnostic criteria derived from individuals with mutations in PKD1. Families with mutations in PKD2 typically have less severe disease, suggesting a potential need for different diagnostic criteria. In this study, 577 and 371 at-risk individuals from 58 PKD1 and 39 PKD2 families, respectively, were assessed by renal ultrasound and molecular genotyping. Using sensitivity data derived from genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
448
0
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 618 publications
(483 citation statements)
references
References 31 publications
2
448
0
15
Order By: Relevance
“…A clinical diagnosis can be difficult to make in young patients, those without a family history and those with relatively fewer cysts on imaging studies. 17 A more cost-effective and accurate molecular diagnostic test, which this technique has the potential to offer, would provide diagnostic certainty for this cohort of patients, thus avoiding serial imaging and periods of diagnostic uncertainty. A genetic diagnosis also adds clarity in the setting of living-related kidney donation, ensuring a phenotypically normal donor does not carry a pathogenic familial variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical diagnosis can be difficult to make in young patients, those without a family history and those with relatively fewer cysts on imaging studies. 17 A more cost-effective and accurate molecular diagnostic test, which this technique has the potential to offer, would provide diagnostic certainty for this cohort of patients, thus avoiding serial imaging and periods of diagnostic uncertainty. A genetic diagnosis also adds clarity in the setting of living-related kidney donation, ensuring a phenotypically normal donor does not carry a pathogenic familial variant.…”
Section: Discussionmentioning
confidence: 99%
“…Patients, over the age of 18, with a diagnosis of ADPKD made based on standard clinical and imaging criteria 17 were prospectively recruited into the study. For those without a family history of ADPKD, a presumptive diagnosis of ADPKD was made if multiple bilateral renal cysts were seen on ultrasound images and there were no manifestations suggestive of another cystic kidney disease.…”
Section: Methodsmentioning
confidence: 99%
“…Kidney disease severity, including ESRD and survival status, was also collected from all available affected family members. The diagnosis of ADPKD in the study subjects was confirmed by ultrasound-based criteria 28 and/or mutation screening. For patients without a positive family history, the diagnosis of ADPKD required the presence of $10 cysts in each kidney, with both kidneys .15 cm in length.…”
Section: Study Protocol and Populationmentioning
confidence: 99%
“…Ultrasound is sufficient to make the diagnosis, and although the measurement of length is imprecise, it suffices for prognosis (26). Criteria for the diagnosis of ADPKD in subjects at risk have been developed based on the prevalence of sporadic cysts (27). Acquired cystic disease is associated with advanced CKD and easily distinguished from ADPKD on the basis of kidney size.…”
Section: Cystic Kidney Diseasementioning
confidence: 99%